Ce K edge XAS of ceria-based redox materials under realistic conditions for the two-step solar thermochemical dissociation of water and/or CO2. Issue 40 (28th September 2015) - Rothensteiner, Matthäus; Sala, Simone; Bonk, Alexander; Vogt, Ulrich; Emerich, Hermann; van Bokhoven, Jeroen A.
Abstract : X-ray absorption spectroscopy was used to characterise ceria-based materials under realistic conditions present in a reactor for solar thermochemical two-step water and carbon dioxide splitting. Abstract : X-ray absorption spectroscopy was used to characterise ceria-based materials under realistic conditions present in a reactor for solar thermochemical two-step water and carbon dioxide splitting. A setup suitable for in situ measurements in transmission mode at the cerium K edge from room temperature up to 1773 K is presented. Time-resolved X-ray absorption near-edge structure (XANES) data, collected for a 10 mol% hafnium-doped ceria sample (Ce0.9 Hf0.1 O2− δ ) during reduction at 1773 K in a flow of inert gas and during re-oxidation by CO2 at 1073 K, enables the quantitative determination of the non-stoichiometry δ of the fluorite-type structure. XANES analysis suggests the formation of the hexagonal Ce2 O3 phase upon reduction in 2% hydrogen/helium at 1773 K. We discuss the experimental limitations and possibilities of high-temperature in situ XAS at edges of lower energy as well as the importance of the technique for understanding and improving the properties of ceria-based oxygen storage materials for thermochemical solar energy conversion.